Acting Out Nazi Germany: A Role-Play Simulation For The History Classroom - Monahan, W. Gregory (Teaching History: A Journal of Methods, 2002)
The scene I confronted when I arrived in the classroom on that third day of the simulation unnerved me. Festooned all over the walls, the blackboard, the backs of chairs, and the door through which I had entered were photocopied political posters, some in full color, most in black and white, all sporting an array of frightening images from Germany in 1932: swastikas, hammers and sickles, pictures of Adolf Hitler and Karl Marx, a Socialist Party poster with a worker crucified upon a devilish swastika, invocations to vote for this candidate or that one, threats of dire consequences should one or the other side prevail. I quickly closed the windowed door and blocked it, fearful that a colleague or a student might happen by, glance in, and wonder what I was teaching these students. Students moved me out of the way and papered the door window with even more posters, and I confronted the unforeseen consequence of an improvisation. On a whim, at the end of the first day of a three-day simulation of the German Reichstag election of 1932, I had promised an extra 300 votes to whichever party put up the most posters on the third day, and my students had responded with ferocious energy! Well, I thought, that idea was obviously going to require a little bit of tweaking.1